STRATEGI PEMBELAJARAN PAI DIMASA PANDEMI COVID 19 DENGAN MEMANFAATKAN GOOGLE CLASSROOM: (STUDI KASUS DI SMK PGRI 3 KARAWANG JAWA BARAT) - Encep Suryana; Pauzan Haryono; Asep Dudin Latif (Cross-border, 2021)
The background of the problem is that the Covid 19 pandemic has an impact on PAI learning strategies utilizing Google Classroom, problems in the field are encountered. Signal disturbances, unstable Internet facilities. The ability of PAI teachers to take advantage of Science and Technology (IT) to make online classes, enter PAI materials. Asking questions to students in the Google Classroom application and students having limited Internet Signal, Internet Quota/Credit. Not yet proficient in learning with Google Classroom. The purpose of this research is to make active student learning strategies and utilize Google Classroom effectively maximum, so that KKM PAI is achieved. The research method used is descriptive with a qualitative approach. Through interviews, observations and documentation studies. The data comes from interview scripts, field notes, photos, videos, tapes, personal documents, notes or memos, and other official documents. The results of the research are that the PAI learning strategy for active students has been implemented. Reduce student interest in learning Google Classroom into a solution to be used as a learning medium for students and teachers using the Google Meetings Application, students achieve completeness in learning KKM according to a predetermined program, PAI teachers first prepare a syllabus, lesson plan (RPP) material, media, methods and student evaluation at SMK PGRI 3 Karawang, West Java.